Language and Culture in Eighteenth Century Russia - Zhivov, Victor (Studies in Russian and Slavic Literatures, Cultures, and History, 2009)
Victor Zhivov's Language and Culture in Eighteenth-Century Russia is one of the most important studies ever published on eighteenth-century Russia. Historians and students of Russian culture agree that the creation of a Russian literary language was key to the formation of a modern secular culture, and this title traces the growth of a vernacular language from the "hybrid Slavonic" of the late seventeenth century through the debates between "archaists and innovators" of the early nineteenth century. Zhivov's study is an essential work on the genesis of modern Russian culture; the aim of this translation is to make it available to historians and students of the field.